Angiographical Identification of Intracranial, Atherosclerosis-Related, Large Vessel Occlusion in Endovascular Treatment - Baek, Jang-Hyun; Kim, Byung Moon (Frontiers in Neurology, 2019)
Identification of intracranial, atherosclerosis-related, large vessel occlusion (ICAS-LVO) is important to set up an optimal endovascular treatment strategy, as most ICAS-LVOs require specific endovascular modalities for efficient recanalization. However, there is currently no decisive way to identify ICAS-LVO for endovascular treatment. Instead of the few, non-specific, clinical and imaging findings that operators have depended on, this review focused on the occlusion type, one of angiographical methods to identify the ICAS-LVO. Occlusion type was originally devised for predicting procedural details and endovascular outcomes of ICAS-LVO. Among occlusion types, truncal-type occlusion is regarded as a surrogate marker for ICAS-LVO. Although rare, false positives or negatives in truncal-type occlusion are possible. Nonetheless, occlusion type was easy to apply and reliably predictive of procedural outcomes. Furthermore, occlusion type can be determined prior to the procedure, which could allow it to be more helpful in setting up an optimal strategy before starting endovascular treatment.